Safety evaluation and antihyperglycaemic effect of root extract of Maerua decumbens (Brongn.) DeWolf in Wistar rats - Richard T. Kiptisia; Geoffrey K. Maiyoh; Benson N. Macharia; Vivian C. Tuei (Scientific African, 2020)
Local communities living in rural regions of Kenya use the plant, Maerua decumbens (Brongn.) DeWolf for various purposes including water purification (roots), as food (roots and fruits) and medicinal (various parts of the plant) for treatment of several ailments including diabetes mellitus. However, there is no scientific evidence on the safety and antidiabetic claims of Maerua decumbens roots despite its continued use. Therefore, this study aimed at evaluating oral acute and sub-acute toxicity of methanolic root extract of Maerua decumbens (400 and 800 mg/kg.b.w/day) in Wistar rats and also the antihyperglycaemic activity of the orally-administered extract in streptozotocin (STZ) induced diabetic rats. Phytochemicals were qualitatively analysed using standard procedures while the fingerprint chromatograph of the extract was revealed by high performance liquid chromatography (HPLC). Diabetes was induced in the experimental groups by single intraperitoneal injection of STZ at 50 mg/kg.b.w. Animal grouping was then done as follows; Groups 1: Normal control; 2: Normal on extract (400 mg/kg.b.w/day) 3; diabetic untreated control; 4, 5 & 6; diabetic treated with 100 and 400 mg/kg.b.w/day of root extract and metformin at 100 mg/kg.b.w/day, respectively. Effects of extract on fasting blood glucose (FBG) and body weights were monitored weekly in the 21 days anti-diabetic study. Also, liver malondialdehyde (MDA) levels were determined at the end of the treatment. For sub-acute toxicity studies, the extract did not affect organ weights of liver, kidney, heart and spleen and there were no pathological changes in the liver and kidney. Also, the blood biochemical and haematological parameters did not show any changes in all dosages although there were significant alterations in red blood cell’ indices but the values were within the published normal reference ranges for the species. Thus the extract was found to be relatively safe after oral sub-acute treatment in rats. On the other hand, the phytochemical-rich extract as also exhibited by the UV spectra of the compounds on diabetic rats showed a marginal increase in body weight, significant decreases in FBG and liver MDA levels versus untreated diabetic rats (p < 0.05). Therefore, Maerua decumbens root extract has great potential for use as a safe alternative medicine for the management of diabetes mellitus due to its antihyperglycaemic effects and reduction in hepatic lipid peroxidation.